Evaluating environmental impacts of thorium extraction: A comparative study of solvent and electrosorption technologies using life cycle assessment (LCA) - Naseem Akhtar; Aznan Fazli Ismail; Marlia Mohd Hanafiah; Syazwani Mohd Fadzil; Sulgiye Park (Cleaner Engineering and Technology)
Thorium extraction techniques, such as solvent extraction from monazite and electrosorption techniques from water leach purification (WLP) of radioactive waste residues, are important for thorium recovery, particularly in Malaysia. Despite their importance, previous studies have largely overlooked critical issues like radioactive hazards, human health risks, and environmental impacts associated with advanced thorium extraction methods. This study addresses these gaps by quantifying the environmental impact associated with solvent extraction and electrosorption techniques using a life cycle assessment (LCA) framework to compare environmental indicators for thorium recovery from monazite ore and WLP residues. The LCA was conducted from cradle to gate, incorporating inventory data from the Ecoinvent database 3 and SimaPro software version 9, with inputs of raw material extraction, transportation, energy consumption, and chemical uses. Emissions into air, water, and soil were quantified across all processing phases. The LCA midpoint findings reveal that thorium disulfate in monazite processing is the key contributor to global warming, producing 45 kg CO2-eq, whereas transportation and electricity consumption also considerably affect emissions, contributing 25.07 kg CO2-eq and 26.17 kg CO2-eq, respectively. Comparative analysis of midpoint indicators showed that solvent extraction had a more significant environmental impact than electrosorption in the context of human carcinogenic toxicity, freshwater ecotoxicity, and marine ecotoxicity. The damaged assessment highlighted endpoint indicators that monazite processing had a higher impact than WLP on human health (0.0364–0.0016 DALY), ecosystems (0.0016–0.0005 species·yr), and resources (0.0012–0.0005 USD, 2013), primarily due to the use of chemicals and emissions. Our study shows that electrosorption from WLP demonstrates superior environmental sustainability compared with solvent extraction from monazite, positioning it a more viable and efficient approach for radioactive waste treatment.